THE IMPACT OF NON-PHARMACEUTICAL INTERVENTIONS ON FIRMSâ FINANCIAL PERFORMANCE AND STOCK RETURNS - Fikri, Muhamad
The COVID-19 is still far from over. A new variant, omicron, was even found in late 2021. The COVID-19, as a global disaster, has influenced our daily life. The COVID-19 pandemic has its effect on the business sector. To control the spread of the COVID-19 pandemic, the Indonesian government has had several policies, such as large-scale social restrictions (LSSR). As a side effect of this policy, a decrease in economic activities was found. This research seeks to investigate how the government response to the COVID-19 pandemic affects firms’ financial performance and stock returns. This research used panel data regression to analyze the data. The difference-in-difference method was also used to seek the causal relationship between the imposed LSSR and firms’ financial performance. The Generalized Method of Moments (GMM) is employed in the robustness test. The results show that the imposed LSSR negatively affects firms’ financial performance represented by ROA. It is also found that the LSSR did not have significant effect on firms’ performance in non-essential firms, which indicates that a decrease in financial performance is found in both essential and non-essential firms. Government policies on containment and closure measure affect stock returns negatively. On the other hand, economic supports provided by the government positively affect the stock returns. From the results, this research can contribute to the literature to see the effect of the large-scale social restrictions on firms’ financial performance and government response on stock returns. This research can also be used as a consideration for the government in making future policies to prevent the spread of the COVID-19 pandemic. Investors can also consider this research while they decide how to react to newly announced policies. Future research could investigate more intraday transaction data and take into account people’s perceptions regarding the condition of the COVID-19 pandemic.